Management of Male Infertility with Coexisting Sexual Dysfunction: A Consensus Statement and Clinical Recommendations from the Asia-Pacific Society of Sexual Medicine (APSSM) and the Asian Society of Men’s Health and Aging (ASMHA) - Eric Chung; Jiang Hui; Zhong Cheng Xin; Sae Woong Kim; Du Geon Moon; Yiming Yuan; Koichi Nagao; Lukman Hakim; Hong-Chiang Chang; Siu King Mak; Gede Wirya Kusuma Duarsa; Yutian Dai; et al. (The World Journal of Men's Health, 2024)
Male infertility (MI) and male sexual dysfunction (MSD) can often coexist together due to various interplay factors such as psychosexual, sociocultural and relationship dynamics. The presence of each form of MSD can adversely impact male reproduction and treatment strategies will need to be individualized based on patients’ factors, local expertise, and geographical socioeconomic status. The Asia Pacific Society of Sexual Medicine (APSSM) and the Asian Society of Men’s Health and Aging (ASMHA) aim to provide a consensus statement and practical set of clinical recommendations based on current evidence to guide clinicians in the management of MI and MSD within the Asia-Pacific (AP) region. A comprehensive, narrative review of the literature was performed to identify the various forms of MSD and their association with MI. MEDLINE and EMBASE databases were searched for the following English language articles under the following terms: “low libido”, “erectile dysfunction”, “ejaculatory dysfunction”, “premature ejaculation”, “retrograde ejaculation”, “delayed ejaculation”, “anejaculation”, and “orgasmic dysfunction” between January 2001 to June 2022 with emphasis on published guidelines endorsed by various organizations. This APSSM consensus committee panel evaluated and provided evidence-based recommendations on MI and clinically relevant MSD areas using a modified Delphi method by the panel and specific emphasis on locoregional socioeconomic- cultural issues relevant to the AP region. While variations exist in treatment strategies for managing MI and MSD due to geographical expertise, locoregional resources, and sociocultural factors, the panel agreed that comprehensive fertility evaluation with a multidisciplinary management approach to each MSD domain is recommended. It is important to address individual MI issues with an emphasis on improving spermatogenesis and facilitating reproductive avenues while at the same time, managing various MSD conditions with evidence-based treatments. All therapeutic options should be discussed and implemented based on the patient’s individual needs, beliefs and preferences while incorporating locoregional expertise and available resources.